Peningkatan Kemampuan Bahasa Inggris Tingkat Dasar Berbantuan Media Worksheet Melalui English Fun - Hatami, Faula Anis; Romadhina, Lailatul; Ratnawati, Nurul; Nuroh, Lailatun; Khusna, Nadiya Hidayatul; Mubarok, Nurhadi (Journal Of Human And Education (JAHE), 2024)
This program is designed to enhance the fundamental English language skills of children in rural regions. The initiative addresses the issue of low English proficiency among elementary school children, which can be attributed to various factors such as limited educational resources, unsuitable learning materials, and ineffective teaching methods. The program employs a community service approach that is both participatory and educational, encompassing three stages: preparation, implementation, and evaluation. Findings from the study indicate a significant improvement in the children's basic English proficiency following their participation in the program. This service activity demonstrates that employing worksheet media through the English Fun initiative can effectively develop basic English skills in children from rural areas. Keywords: Community Service, English Fun, Worksheet